Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

The interactive role of concentrated freshly squeezed tea juice supplementation on structural and in vitro digestibility of dried Nigari tofu - Mei-Xuan He; Ibrahim Khalifa; Xiao-Min Zeng; Jian Zheng; Wen Zhang; Zhu-Cheng Su; Noman Walayat; Ran Wei (Food Chemistry, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Novel photoelectron-driven nitrate reduction in anammox granules using photosensitive semiconductor iron mineral for wastewater treatment - Xue Wang; Tao Xue; Jian Li; Caiyun Zhang; Guizhen Hao; Yuzi Xing; Ran Tao; Lin Guo; Haozhe Zhang; Shu Chai; Lei Zheng (Water Research, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

High-Frequency Signal Recovery via the Constraint of Reflection Structure in f-x Domain - Chong Sun; Nan-ying Lan; Duo-ming Zheng; Hao-nan Tian; Shi-kai Jian; Lang Yang; Zhi-fang Ran; Rui-dong Liu (Applied Geophysics, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The transcriptional regulatory module MdERF2-MdSCR11 promotes ABA-mediated apple fruit ripening through synergistic repression of MdABA4-2 - Miaomiao Wang; Qizhe Li; Hao Wang; Nan Jiang; Jiale Wang; Xiaotong Hu; Yu Liu; Tuanhui Bai; Jian Jiao; JiangLi Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Integrated transcriptomic and physiological analysis highlights the candidate genes regulating enzymatic browning, antioxidant capacity, and lipid metabolism in pomegranate aril browning - Yawen Shen; Sen Wang; Ran Wan; Jian Jiao; Yujie Zhao; Liu Cong; Kunxi Zhang; Pengbo Hao; Yu Liu; Wanyu Xu; Miaomiao Wang; Jiangli Shi; et al. (Postharvest Biology and Technology, 2026)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Evaluating the effects of a pectinolytic probiotic strain as replacement of enzymatical treatments in melon juice pre-alcohol fermentation - Haoyu Niu; Xilong Zhou; Chenang Lyu; Dapeng Wang; Jian Zheng; JiYu Cheng; Ran An (International Journal of Food Microbiology, 2025)

Tidal influence on residual saltwater removal behind subsurface dams in unconfined coastal aquifers - Tianyuan Zheng; Ran Cao; Yunhai Fang; Jian Luo; Peihua Li; Xilai Zheng; Xiuyu Liang; Tao Liu; Marc Walther (Journal of Hydrology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

MdAP2-like, a new regulator in apple, simultaneously modulates fruit softening and size - Miaomiao Wang; Wenduo Zhan; Ming Chen; Yanfei Guo; Hao Wang; Yao Wu; Tuanhui Bai; Jian Jiao; Chunhui Song; Jiangli Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Identifying cadmium and lead co-accumulation from living rice blade spectrum - Shuangyin Zhang; Teng Fei; Yiyun Chen; Jiaxin Yang; Ran Qu; Jian Xu; Xiao Xiao; Xuejun Cheng; Zhongzheng Hu; Xuedong Zheng; Dengzhong Zhao (Environmental Pollution, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Advances in the application of metallic isotopes to the identification of contaminant sources in environmental geochemistry - Peng Wang; Jian Hu; Tingyi Liu; Jinke Liu; Shunrong Ma; Wenmin Ma; Jun Li; Houyi Zheng; Ran Lu (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Molecular phylogenetics and population demographic history of Amphioctopus fangsiao, inferred from mitochondrial and microsatellite DNA markers - Jian Zheng; Yan Tang; Ran Xu; Xiaoying Zhang; Xiaodong Zheng (Acta Oceanologica Sinica, 2023)

C4 expansion of Central Asia in the middle Miocene linked to the strengthening Indian monsoon - Jian Wang; Xinying Zhou; Shiqi Wang; Hai Xu; Hermann Behling; Jie Ye; Yan Zheng; Junchi Liu; Yan Wu; Keliang Zhao; Ran Zhang; Xiaoqiang Li (Global and Planetary Change, 2023)

Nocardia seriolae mediates liver granulomatous chronic inflammation in Micropterus salmoides through pyroptosis - Zheng‐Yang Zhou; Shang‐Jie Bai; Chen‐Wang Lu; Bin Yang; Jun Wang; Sheng Lian; Zheng‐Ran Jian; Er‐Long Wang; Gao‐Xue Wang; Tao Liu (Journal of Fish Diseases, 2023)
Granulomatous diseases caused by Nocardia seriously endanger the health of cultured fish. These bacteria are widely distributed, but prevention and treatment methods are very limited. Chronic granulomatous inflammation is an important pathological feature of Nocardia infection. However, the molecular mechanisms of granuloma formation and chronic inflammation are still unclear. Constructing a granuloma infection model of Nocardia is the key to exploring the pathogenesis of the disease. In this study, we established a granuloma model in the liver of largemouth bass ( Micropterus salmoides ) and assessed the infection process of Nocardia seriolae at different concentrations by analysing relevant pathological features. By measuring the expression of pro‐inflammatory cytokines, transcription factors and a pyroptosis‐related protein, we revealed the close relationship between pyroptosis and chronic inflammation of granulomas. We further analysed the immunofluorescence results and the expression of pyroptosis‐related protein of macrophage infected by N. seriolae and found that N. seriolae infection induced macrophage pyroptosis in vitro. These results were proved by flow cytometry analysis of infection experiment in vivo. Our results indicated that the pyroptosis effect may be the key to inducing chronic inflammation in the fish liver and further mediating granuloma formation. In this study, we explored the molecular mechanism underlying chronic inflammation of granulomas and developed research ideas for understanding the occurrence and development of granulomatous diseases in fish.

Enhanced washing of cadmium and lead from polluted river sediment using horizontal electroosmosis - Ran Wen; Xiong Yang; Shuang He; Jian Wu; Hongmei Ge; Zheng Chi; Yafei Shi; Shulian Wang; Andrea R. Gerson; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

The preparation of dodecyl trimethyl ammonium bromide modified titanium dioxide for the removal of uranium - Jian Wang; Ran Ma; Zheng Jiang (Environmental Science and Pollution Research, 2022)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

A new sesquiterpene from the gorgonian coral Menella sp. - Qi Peng; Fen Liu; Huan Sun; Xiao-Jian Liao; Mei-Ran Feng; Ting-Ting Liu; Zheng-Xiong Xu; Jun Zhang; Shi-Hai Xu (Natural Product Research, 2016)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Ultrasound-Microbubble Transplantation of Bone Marrow Stromal Cells Improves Neurological Function after Forebrain Ischemia in Adult Mice - Zili Gong; Hong Ran; Shengzheng Wu; Jie Zhu; Jian Zheng (Cell Biochemistry and Biophysics, 2014)

Effects of the Metals Lead and Zinc on the Growth, Development, and Reproduction of Pardosa Astrigera (Araneae: Lycosidae) - Xiao-qiong Chen; Zheng-tian Zhang; Ran Liu; Xiu-Ling Zhang; Jian Chen; Yu Peng (Bulletin of Environmental Contamination and Toxicology, 2011)